If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 = -5(1 + 3x) 85 = (1 * -5 + 3x * -5) 85 = (-5 + -15x) Solving 85 = -5 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 85 + 15x = -5 + -15x + 15x Combine like terms: -15x + 15x = 0 85 + 15x = -5 + 0 85 + 15x = -5 Add '-85' to each side of the equation. 85 + -85 + 15x = -5 + -85 Combine like terms: 85 + -85 = 0 0 + 15x = -5 + -85 15x = -5 + -85 Combine like terms: -5 + -85 = -90 15x = -90 Divide each side by '15'. x = -6 Simplifying x = -6
| 4.9t^2-18t+15=0 | | n^2+20n=-100 | | 2a=4a-2a+4 | | 6y-12-3y+8=0 | | 12(0)+8y=5 | | 4(5x-4)=8x+2 | | N+-16=-8 | | 110000=1285.3(t)+48207 | | P=2(x+y) | | 10(x+3)-(-9x)=x-5+3 | | -6x-24=5x | | 7e+4e+1=36 | | -5(2y-5)-y=-3(y-4) | | 5x+6(x-14)=5(x-12) | | 5x+10=4x-2 | | 10x-12=2-18x | | 3x+19=23+8x | | 10x-6=7x+8 | | -5(8p+3)-6= | | 3x+x=25-1 | | 3x^2=20y | | 5g+12g=21-g | | E=y+z+xm | | 2x+3x-20= | | 37x+19=6(6x+7) | | -4(2(0)-3)=12-8(0) | | -7z+1=9 | | 0=-19x-6y+2 | | 5y+3(y-5)=4(y+1)-2 | | a=-10+1bi+6i | | 12(0)+8x=5 | | 0.8v+19.65+17v=18.1v+19.11 |